(3HQfGeL ebJQM dGSJMOGK UjGZGJ JTcjdjI ai GdNRa ef NdGd Gdaf GdeaGgjej (B: s (3OQGSI JLQjHjI (B/ s - (3ei eMeO SYjO YHO GdQMef eMQes; (3GMeO SjO eQSi (B: s; (3ceGd UahJ (B: s; (3eDefI eeOhM cGed (B: s ((3GdbGgQI (B: s (3ei eMeO SYjO YHO GdQMef eMQe (B: s, 2015)
(3jJfGhd GdHMK JUeje HQfGeL ebJQM dJOQjS GdNRa dWdGH GdaQbI GdQGHYI HcdjI GdJQHjI GdfhYjI LGeYI GdbGgQI ef NdGd Gdaf GdeaGgjej dEjLGO eOGNd LOjOI JSge aj JhSjY BaGb GdJacjQ hGdGHJcGQ Yf GdWdGH(B. (3hGSJgOaJ GdOQGSI GdMGdjI(B: 1-(3GYOGO HQfGeL bGFe Ydj GdCJLGg GdeaGgjej dJOQjS GdNRa ddaQbI GdQGHYI HcdjI GdJQHjI GdfhYjI LGeYI GdbGgQI(B. 2-(3GjLGO eOGNd JLQjHjI LOjOI JYJeO Ydj JMbjb Gdeaghe aj GdNRa dGSJMOGK JTcjdGJ NRajI LOjOI(B. (3hYdjg abO GaJQVJ GdOGQSI GdaQhV GdJGdjI (B:(3jecf GSJMOGK UjGZGJ JTcjdjI LOjOI ddTcd GdNRaj ef NdGd Yed HQfGeL ebJQM dOQGSI GdCSS hGdCSGdjH hGdCJLGgGJ Gdafjg ddaf GdeaGgjej s
(3GWQhMI (B((3eGLSJjQ (B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdafjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdNRas; (3Gdaf GdeaGgjei s; (3UjGZGJ JTcjdjI s